Psychological and Spiritual Well Being Serta Kualitas Tidur Pasien kanker yang Menjalani Kemoterapi - Natalia M, Adriani; Sembiring, Erika Emina; Ahmad , Musfira (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
Psychological Well-Being, spiritual Well-Being and sleep quality aspects are known to influence the well-being and quality of life of cancer patients. The aim of this study was to evaluate the psychological aspects, spiritual aspects and sleep quality of cancer patients undergoing chemotherapy. Quantitative research method with exploratory descriptive research design. The research samples were patients who were undergoing chemotherapy at RSUP Prof. Dr. R. D. Kandou totaled 92 respondents using purposive sampling technique. The instruments used were the 42-item Psychological Well-Being Scale, spiritual Well-Being Scale (SWBS), Pittsburg Sleep Quality Index (PSQI). The results showed that the highest number of Psychological Well-Being was in the High category with 70 respondents (76.1%), the highest number of Spiritual Well-Being respondents was in the medium category, namely 56 people (60.9%) and the sleep quality of cancer patients was the highest in bad category, namely 66 (71.7%). In conclusion, health care providers must provide support and attention to patients in these three aspects in order to improve the patient's quality of life.